2022
DOI: 10.3171/2021.10.spine21728
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of restenosis after lumbar decompression surgery: decompression versus decompression and fusion

Abstract: OBJECTIVE The aim of this study was to compare perioperative complications and postoperative outcomes between patients with lumbar recurrent stenosis without lumbar instability and radiculopathy who underwent decompression surgery and those who underwent decompression with fusion surgery. METHODS For this retrospective study, the authors identified 2606 consecutive patients who underwent posterior surgery for lumbar spinal canal stenosis at eight affiliated hospitals between April 2017 and June 2019. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, this process usually takes months to years. 36 Early reoperation is mainly attributed to surgical complications or untreated pre-existing degeneration, which may explain why the disc degeneration grade was not associated with early reoperation in this study.…”
Section: Discussionmentioning
confidence: 65%
“…However, this process usually takes months to years. 36 Early reoperation is mainly attributed to surgical complications or untreated pre-existing degeneration, which may explain why the disc degeneration grade was not associated with early reoperation in this study.…”
Section: Discussionmentioning
confidence: 65%
“…However, these studies have low sample sizes <100. [ 36 - 38 ] One hypothesis for this increased in mortality with fusion is that patients requiring these surgeries were unhealthier overall, and thus had increased mortality when compared to decompression patients. Indications for fusion include traumatic causes, infection, tumor, and spinal disease causing instability, which may not be present in patients undergoing only decompression.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for rLDH include obesity, age, disc height index, Modic changes, sagittal range of motion, and adjacent segment degeneration (11)(12)(13). However, the all-cause recompression of the spinal canal or nerve root after surgical treatment of DLSS, which accounts for 52.1%-100% of reoperation cases (14), has not been fully investigated. Haimoto (15) reported that a decrease in disc height or progression of disc wedging was a risk factor for recompression after microscopic decompression; however, the sample size was relatively small (7 in the recompression group).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the treatment of recompression is more complicated. Although many studies have considered spinal fusion the optimal revision choice (19)(20)(21)(22), some clinicians support minimally invasive and non-fusion concepts to reduce surgical trauma (14,23), especially for those without lumbar instability. However, whether PTED can achieve better efficacy than traditional spinal fusion has not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation